(untitled) (Research, Society and Development, 2021)
The concept of style in pedagogical language is often used to address the different types of behaviors that are united in a single stereotype, which somehow becomes useful for classification and behavioral analysis. Thus, the work aimed to characterize the styles and learning strategies among university students of the undergraduate course in Pharmacy. The work was carried out in two stages: First, the theoretical foundation on the teaching-learning process was carried out; Afterwards, the characterization of the learning strategies was carried out using the LASSI (Learning and Study Strategies Inventory) questionnaire and, for the characterization of the learning styles, the ILS instrument (Index of Learning Styles). The results presented did not demonstrate teaching-learning relationships during graduation time in relation to learning strategies. While, the most observed learning styles were the sensory/intuitive styles. In addition, there was a predominance among students of sensory, visual and sequential styles, with the less frequent style among students, the intuitive. In view of the data presented, one can observe the scarcity of studies that assessed learning styles or strategies among Brazilian university students. Therefore, further investigations are needed in the field of pharmacy to verify more details about factors and their relationships with the use of these learning styles and strategies in the academic growth of students.